1995
DOI: 10.1074/jbc.270.46.27653
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mitotic Specific Phosphorylation Site of Histone H1

Abstract: 32P-Labeled histone H1 was isolated from synchronized Chinese hamster (line CHO) cells, subjected to tryptic digestion, and fractionated into 15 phosphopeptides by high performance liquid chromatography. These phosphopeptides were grouped into five classes having different cell cycle phosphorylation kinetics: 1) peptides reaching a maximum phosphorylation rate in S and then declining in G 2 and M, 2) peptides reaching a maximum phosphorylation rate in G 2 and then remaining constant or declining in M, 3) pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 31 publications
1
41
1
3
Order By: Relevance
“…A number of proteins are subjected to mitosis-specific phosphorylation, which in most cases is involved with p34 cdc2 kinase (22,36,40). To test whether the p34 cdc2 kinase might be involved in phosphorylation of EBNA-2, we carried out in vitro kinase assays by using purified p34 cdc2 kinase.…”
Section: Resultsmentioning
confidence: 99%
“…A number of proteins are subjected to mitosis-specific phosphorylation, which in most cases is involved with p34 cdc2 kinase (22,36,40). To test whether the p34 cdc2 kinase might be involved in phosphorylation of EBNA-2, we carried out in vitro kinase assays by using purified p34 cdc2 kinase.…”
Section: Resultsmentioning
confidence: 99%
“…A correlation between the phosphorylation of H1 histones and mitotic chromosome condensation was further demonstrated by treatment of mammalian cells with the kinase inhibitor staurosporine and with the DNA-binding dye Hoechst 33342, respectively. Both substances not only prevented H1 histone phosphorylation, but also entry into mitosis (Th'ng et al, 1994;Gurley et al, 1995). When murine cells were blocked in mitosis with nocodazole, the addition of staurosporine caused rapid H1 histone dephosphorylation accompanied by chromosome decondensation (Th'ng et al, 1994).…”
Section: Posttranslational Modificationmentioning
confidence: 97%
“…When investigating Chinese hamster ovary cells Gurley et al (11) found that in interphase histone H1 is phosphorylated exclusively in the C-terminal region and that during mitosis only it is also phosphorylated in the N-terminal end. With regard to H1 interphase phosphorylation the authors supposed that there is no qualitative cell cycle specificity as to which site is phosphorylated first and that the number of phosphates per H1 molecule is more important than which sites are phosphorylated.…”
Section: Discussionmentioning
confidence: 99%
“…The p34cdc2/cyclin B kinase, having maximum activity at mitosis (10), was expected to be the enzyme responsible for phosphorylation of the mitotic-specific serine and threonine sites of histone H1. Surprisingly, in Chinese hamster ovary cells mitotic-specific phosphorylation of both serine and threonine residues was found to be located at the end of the N-terminal region of H1, which has no (S/T)PXZ consensus sequences (11). Only few data exist about site-specific phosphorylation during interphase.…”
mentioning
confidence: 99%
See 1 more Smart Citation